2020
DOI: 10.1111/dth.13566
|View full text |Cite
|
Sign up to set email alerts
|

Overview of herbal and traditional remedies in the treatment of cutaneous leishmaniasis based onTraditional Persian Medicine

Abstract: This study aims to describe the herbal and traditional remedies in the treatment of cutaneous leishmaniasis (CL) with an overview on related available evidence in modern medicine. This study is a review that focuses on the most important Traditional Persian Medicine (TPM) sources including Avicenna's Canon of Medicine, Jorjani's Zakhīra‐yi Khārazmshāhī, and Aazam‐Khan's Eksir‐e‐Aazam, as well as pertinent information from Embase, PubMed, Scopus, Scientific Information Database, and Google Scholar by using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Ulcer is disruption of continuity occurring in flesh and its surroundings which may become purulent 17 . This skin condition, that is, frequently mentioned in TPM sources, is known as “ Qoruh ” and “ Rish ,” and has various types, such as “ Sa'fah ,” “ Nar ol‐farsi ,” “ Rish‐e‐balkhi ,” and leprosy 8,25,26 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Ulcer is disruption of continuity occurring in flesh and its surroundings which may become purulent 17 . This skin condition, that is, frequently mentioned in TPM sources, is known as “ Qoruh ” and “ Rish ,” and has various types, such as “ Sa'fah ,” “ Nar ol‐farsi ,” “ Rish‐e‐balkhi ,” and leprosy 8,25,26 …”
Section: Resultsmentioning
confidence: 99%
“…Nar ol‐farsi is also progressive blistery pimples, accompanied by pruritus and burning, caused by burned bile blended with black bile. Rish‐e‐balkhi is also an ulcer accompanied by crust and pus 17,26 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fractionation of this extract revealed that triterpenoid compounds, in particular, contribute to its antiplasmodial effects [2]. Whereas antimicrobial activities of essential oils are well known in general, reports about the application of Boswellia oleo-gum-resin or its constituents against Leishmaniasis are scarce [5,6]. A commercially available essential oil, mainly obtained from B. carteri alongside further Boswellia spp., showed an IC 50 value of < 12.5 µg/mL against promastigotes and 22.1 ± 4.2 µg/mL against intracellular amastigotes of Leishmania amazonensis [7].…”
Section: Introductionmentioning
confidence: 99%